Thermal-daylighting balance through building shading devices: review on factors and methods / Aimi Zahirah Zulkarnain, Mohd Najib Mohd Salleh and Zalena Abdul Aziz - Zulkarnain, Aimi Zahirah; Mohd Salleh, Mohd Najib; Abdul Aziz, Zalena (Universiti Teknologi MARA, Perak, 2021)
Daylighting is interpreted as natural sunlight allowed into an indoor space. Passive lighting strategies are considered fundamental in achieving a high performing sustainable building, which affects the visual and thermal comfort, and energy performance of a building. Many strategies in controlling daylighting are known, however, the wrong implementation can lead to a negative effect. The results obtained need to reach a balance between daylighting and thermal performance. This review is conducted to analyse the concept and factors that affect the balance through different research parameters. The performance factors include energy, comfort and perception or view. The different methods of achieving the balance are categorized into three, which are parameter relation, combination, and multi-objective optimization. Building shading devices are considered as one of the major solutions to reach thermal-daylighting balance. Through a comprehensive review, adjustable shading control is recommended as a better option for building shading device for buildings to achieve the optimum balance.